Greenland winter tourism in a changing climate. (September 2019) - Schrot, Oliver Gerald; Christensen, Jens Hesselbjerg; Formayer, Herbert
Abstract: Climate change in Greenland is interfering with environmental and human systems at an accelerating rate. Climate-related effects are particularly observable in the Greenlandic tourism sector—which is a designated future key industry. Responding to these changes requires planned efforts for the various tourist seasons. To date, studies investigating how West Greenlandic winter tourism may be affected by Arctic warming remain sparse. Therefore, we used the regional climate model HIRHAM5 at a 5.5 km horizontal resolution for the RCP 8.5 scenario and two time slices (2031–2050 and 2081–2100), relative to the modelled historical period (1991–2010) to characterize the consequences of business-as-usual warming on recreational winter activities (i.e., resort skiing, ski-touring, heli-skiing, cross-country skiing, dog sledding, snowmobiling and trophy hunting). Study locations included Nuuk, Ilulissat, Sisimiut and Kangerlussuaq. Model data provide strong evidence for increasing annual mean temperature (between 1.1 °C and 4.6 °C) and precipitation (between 1% and 78%) in West Greenland until 2100, compared to 1991–2010. According to our results, snowfall and snow cover season length decrease (between 34% to 42% and 21% to 49%, respectively) in the long run. Resort skiing and cross-country skiing are affected by snow marginality and wet snow conditions, while ski-touring and heli-skiing demonstrate a higher adaptive capacity (i.e., translocation to snow safe destinations). A reduced snow cover thickness particularly threatens dog sledding. In-depth interviews were conducted with two local stakeholders working in winter tourism. Their perspectives suggested that they will be challenged adapting outdoor recreation by middle and end of the twenty-first century.